A novel and highly sensitive electrochemical monitoring platform for 4-nitrophenol on MnO2 nanoparticles modified graphene surface. Issue 108 (20th October 2015) - Zaidi, Shabi Abbas; Shin, Jae Ho
Abstract : A novel, simple fabrication of a 4-nitrophenol (4-NP) electrochemical sensor using MnO2 nanoparticles modified graphene with high sensitivity and selectivity. Abstract : 4-Nitrophenol (4-NP) has been considered a deadly pollutant causing slow photosynthetic reactions, carcinogenicity and other related serious detrimental effects toward human and aquatic life. In this work, a novel, sensitive and reliable electrochemical sensor was prepared by electrodepositing manganese dioxide nanoparticles (MnO2 -NPs) over reduced graphene oxide (RGO) for the determination of 4-NP. The successful synthesis of graphene oxide (GO), reduced graphene oxide, and MnO2 -NPs were characterized by scanning electron microscopy (SEM). The electrochemical behaviors of 4-NP on MnO2 –RGO/GCE and various other modified electrodes were investigated and compared. It was observed that only the MnO2 –RGO/GCE electrode exhibited well defined redox peak currents toward 4-NP. Under optimized conditions, the reduction peak current varies linearly with the concentration of 4-NP ranging between 0.02–0.5 μM and 2–180 μM and a detection limit (LOD) of 10 nM (S/N = 3) was estimated. Furthermore, the as-fabricated sensor displayed high selectivity, stability, reproducibility and excellent recoveries of 4-NP in various water samples spiked with 4-NP. Thus, the proposed method provides an outstanding platform for the detection of 4-NP with great ease and reliability.